Огненные близнецы: роман: [для сред. шк. возраста] / Сестры Воробей - Сестры Воробей (Романы для девочек, 2003)
Экземпляры: ф. 14 (20140226) / Инвентарный номер: 35411 / Цена: 15.00 / Авт.знак: С 33 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6